(untitled) (Journal of Dialogos, 2026)
The development of digital technology encourages MSMEs to adapt more interactive and experience-oriented marketing communication strategies. One emerging form of digital marketing innovation is live commerce, which enables real-time interactions between businesses and consumers. This study aims to analyze how the implementation of live commerce packaged with a cozy aesthetic approach is used as a marketing communication strategy for MSMEs in building digital consumer loyalty. This study uses a qualitative approach with a descriptive research type through case studies. Research data were obtained through observations of MSMEs’ live commerce practices, analysis of marketing communication patterns, the application of cozy aesthetic visual and emotional elements, and consumer responses in digital interactions. The results show that the integration of live commerce with cozy aesthetics can create a warm, personal, and comfortable communication atmosphere, thereby increasing trust, emotional engagement, and closeness between MSMEs and consumers. This strategy not only has an impact on increasing short-term interactions and transactions but also contributes to building sustainable digital consumer loyalty. Thus, live commerce packaged with a cozy aesthetic approach can be an effective and relevant marketing communication strategy for MSMEs in facing competition in the digital era..